Implementation of the Nahdlatul Ulama’s Brotherhood Trilogy Concept in Pandemic Covid-19 Mitigation - Agus Setiawan; Muhamad Agus Mushodiq; Mosaab Elkhair Edris (KURAS Institute, 2022)
During the Covid-19 pandemic, religious doctrine often clashed with mitigation efforts. This paper aims to interpret the brotherhood trilogy concept initiated by KH. Achmad Siddiq as a guide in mitigating the Covid-19 pandemic. The author relates these guidelines to the mitigation efforts that have been carried out by PCNU Metro Lampung Indonesia. In conducting the research, the authors use qualitative research with data analysis and interpretation according to Miles and Huberman which includes data reduction, data presentation, and data verification. The results of this paper are: First, pandemic mitigation efforts with the brotherhood trilogy are the application of fair ‘wasatiyah’, balance ‘tawazun’, tolerance ‘tasamuh’, and dynamic ‘tatawuriyah’ values. Second, from the perspective of Islamic Brotherhood, the mitigation of the Covid-19 pandemic, carried out by PCNU Metro Lampung Indonesia, includes equalizing the perception of Muslims regarding the nature of the Covid pandemic, education, and distribution of medical or non-medical assistance at the Islamic brotherhood among Nahdlatul Ulama people level ‘Islamic Brotherhood of Nahdliyah’. Third, in the perspective of Nationality Brotherhood, the efforts made are by distributing masks to the general public and spraying disinfectants in public places. Fourth, in the perspective of Humanity Brotherhood, the effort made is in educating to the public so as not to spread hoax news related to the pandemic on social media as a global communication tool